Transcatheter and surgical aortic valve replacement for aortic stenosis in France: Trends from 2010 to 2022 and impact of European guidelines and clinical trial results - Anaïs Havet; Annaëlle Testud; Aubane L’Hospital; Guy De Gevigney; Nicolas Chavanis; Marie Viprey; Xavier Armoiry (PLoS ONE, 2026)
Background The PARTNER trials played a key role in the expansion of transcatheter aortic valve replacement (TAVR) for severe aortic valve stenosis (AS), shaping international practice guidelines. We assessed the evolution of AS management in France between 2010 and 2022, and the impact of PARTNER trials and European guideline updates on TAVR use. Characteristics of patients, facilities and TAVR valves, and post-procedure events were also described. Methods and findings We conducted a nationwide cohort study using the French Health Data System (SNDS), including patients aged 18 years or older hospitalized for AS and receiving a first TAVR or surgical aortic valve replacement (SAVR) from 2010 to 2022. ARIMA models were used to study the impact of PARTNER trials and European guideline updates on TAVR use. Among 255,453 procedures, 109,739 were TAVR (N 2010 : 1,389; N 2022 : 16,770). No significant change in the proportion of TAVR was associated with PARTNER trials or European guideline updates (p ≥ 0.125). Median age and EuroSCORE II proxy were 83.0 years and 2.2 in TAVR group and 72.0 years and 1.4 in SAVR group. Approximately 60% of the TAVR and SAVR procedures were performed in public facilities. Latest valve generations replaced progressively earlier ones, with 62.5% being balloon-expandable. Mortality decreased over time in both groups, while length of stay and intensive care unit admissions decreased only in TAVR group. Conclusions This 13-year nationwide overview highlights the growing uptake of TAVR in France, likely driven by clinical practice and procedural innovation rather than guidelines. Further analyses will compare efficacy and safety between TAVR and SAVR.